Emergence of networks and market institutions in a large virtual economy - Curtis Kephart; Daniel Friedman; Matt Baumer (University of California, Economics Department, 2015)
A complete set of transactions, more than 40 million within a 1.8 year span, allows us to track the evolution of the trader network and the goods network in an on-line trading community. The computer platform was designed to make barter exchange as attractive as possible; money was not part of the design and all players were created equal. Yet, within weeks, several specific goods began to emerge as media of exchange, and not long after that various sorts of specialized traders began to appear. We track their progress using network-theoretic metrics such as node strength, assortativity, betweenness and closeness. By the end of our sample, virtually all trade was money-mediated and market makers played a major role.
Keywords: 330